Digital teaching skills: self-perception report in health sciences - Urrejola-Contreras, Gabriela (2023)
Objective: To determine the level of digital skills among academics who teach first- to fifth-year students of health sciences programs using a self-perception questionnaire during the first semester 2023. Materials and methods: The study used a descriptive and cross-sectional research design. The sample consisted of 63 professors of health sciences programs at Universidad de Viña del Mar, Chile. Digital teaching skills were assessed using the DigCompEdu CheckIn questionnaire and a Likert scale response format. The instrument considered the dimensions professional commitment, digital resources/pedagogy, evaluation and feedback, student empowerment and facilitating students’ digital skills. Data were collected using Google Forms and analyzed with descriptive statistics that included means, standard deviation, coefficient of variation, percentages and frequencies. Results: The results show that the professors, as a whole, achieved an average score of 3.4 in the complete instrument, with a standard deviation of 1.2. This indicates that professors are in an intermediate range in terms of digital teaching skills, thus suggesting that they have a moderate perception of their digital skills. Conclusions: Professionals, in their teaching role, should feel empowered to address online security issues, use digital assessment tools and customize teaching through technology. By doing so, they will be able to provide a more comprehensive and high-quality education in today’s digital age. Therefore, training in digital teaching skills among professors may be a criterion for improving educational quality and students’ training in a world where digital skills play a key role.